Microstructural Controls on Thermal Crack Damage and the Presence of a Temperature‐Memory Effect During Cyclic Thermal Stressing of Rocks. Issue 19 (9th October 2020) - Daoud, Ali; Browning, John; Meredith, Philip G.; Mitchell, Thomas M.
Abstract: We present results from a series of thermal stressing experiments that used three igneous rocks of different composition, grain size, and origin and contemporaneously recorded acoustic emissions (AEs) with changing temperature. Samples were subjected to both a single heating and cooling cycle and multiple heating/cooling cycles to different peak temperatures. The vast majority of thermal crack damage is generated during heating in the coarser‐grained (quartz rich) rock but during cooling in the two finer‐grained (quartz poor) rocks. Our AE results also demonstrate the presence of a temperature‐memory effect, analogous to the Kaiser stress‐memory effect observed during cyclic mechanical loading, but only in the coarser‐grained rock. We suggest that the total amount of crack damage induced during either heating or cooling is dependent on the mineral composition and, most importantly, the grain size and arrangement, as well as the maximum temperature to which the rock was exposed. We use our laboratory‐scale results to suggest ways in which crustal‐scale geophysical data may need to be reinterpreted to provide more accurate estimates of total, accumulated damage and the approach to macroscopic failure in crustal segments hosting magma chambers and geothermal reservoirs. Plain Language Summary: We present results from a series of laboratory thermal stressing experiments using three igneous rocks of different composition, grain size, and origin: a Granophyre (SGP) from the Slaufrudalur pluton in Iceland, an Andesite from Santorini, Greece (SA), and a Basalt from the Seljadalur region of Iceland (SB), in which acoustic emissions (AEs) were recorded at the same time as the temperature of the samples was experimentally increased or decreased. Samples were subjected to both a single heating and cooling cycle and multiple heating and cooling cycles to different peak temperatures. The vast majority of thermal crack damage was generated during heating in the larger‐grained SGP but during cooling in the smaller‐grained SA and SB. Our AE results demonstrate the presence of a temperature‐memory effect in SGP, analogous to the Kaiser stress‐memory effect observed during cyclic mechanical loading, but no similar effect is observed in either SA or SB. We suggest that the total amount of crack damage is dependent on the mineral composition and, most importantly, the grain size and arrangement, as well as the maximum temperature to which the rock was exposed. The results should be considered in models that consider the distribution of damage in cyclically thermally stressed regions such as crustal segments hosting geothermal reservoirs and/or magmatic intrusions. Key Points: The majority of thermal crack damage is produced during heating in the coarse‐grained granophyre but during cooling in the finer‐grained andesite and basalt A temperature‐memory effect is exhibited during thermal cycling in the quartz‐rich granophyre but not in the quartz‐poor andesite or basalt Interpretation of prefailure seismicity in volcanic/geothermal settings needs to take account of damage accumulated in earlier deformation cycles